PERSEPSI IBU RUMAHTANGGA TERHADAP PRODUK TEMPE SORGUM DAN STRATEGI PENGEMBANGANNYA DI KABUPATEN MUSI RAWAS - Puspitasari, May Shiska; Sutejo, Sutejo (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2018)
ABSTRACT This study aims to determine the perception of housewives about processed sorghum tempe product and its development strategies. This research was conducted in Tugumulyo Subdistrict, Musi Rawas District that is a migrant population area, the majority of which originated from tempe (Java). Data collection was carried out from June to July 2017. The method used was survey method, sampling by simple random sampling which total of 50 housewives. The data analyzed through a Likert scale and SWOT analysis. The results showed that the perception of housewives on the sorghum tempe product variable with an index value of 42.4%, a social class variable with an index value of 36.4%, a psychological variable with an index value of 40.2% and a variable purchase decision with an index value of 38, 6%. The S-O strategy, showed the, triggering coordination between the Industry and Trade Agency and the producer group of tempe sorghum, promoting tempe sorghum through electronic mass media, ensuring precise input techniques and in accordance with the type of land. The W-O strategy, showed utilizing the District Governments support to integrate producer and respondent relationships, fostering the total production capacity of sorghum tempe according to the number of respondents growing, looking for sources of sorghum that are ready for processing from other regions. The S-T strategy, showed spurring the several multi-year action research on wet and dry land Musi Rawas district, prioritizes local equipment without chemicals, ensures the use of high-productivity and high-land production techniques and W-T strategies include selecting areas and farmers who are ready to grow sorghum as needed, providing specialized training on hygienic and quality sorghum tempe production, providing a good Sorghum warehouses near the manufacturers.ABSTRAK Penelitian ini bertujuan untuk mengetahui persepsi ibu rumahtangga mengenai produk olahan tempe sorgum dan strategi pengembangannya. Penelitian ini dilaksanakan di Kecamatan Tugumulyo Kabupaten  Musi Rawas. Penentuan lokasi dengan pertimbangan bahwa di daerah tersebut merupakan daerah penduduk pendatang yang mayoritas dari suku asal tempe (Jawa). Pengumpulan data dilaksanakan pada bulan Juni sampai Juli 2017. Metode yang digunakan metode survey, pengambilan sampel secara simple random sampling  Sebanyak 50 orang ibu rumahtangga. Metode pengolahan data menggunakan skala likert dan analisis SWOT. Hasil penelitian bahwa dilihat dari persepsi ibu rumahtangga  terhadap variabel produk tempe sorgum dengan nilai indeks 42,4%, variabel kelas sosial dengan nilai indeks 36,4%, variabel psikologi dengan nilai indeks 40,2%  dan variabel keputusan pembelian dengan nilai indeks 38,6%. Strategi S-O antara lain memicu koordinasi Disperindag dengan kelompok produsen tempe sorgum, mempromosikan tempe sorgum melalui media massa elektronik, memastikan teknik produksi tepat input & sesuai jenis lahan. Strategi W-O antara lain memanfaatkan dukungan Pemerintah Kabupaten untuk memadukan hubungan produsen dan responden, membina kapasitas total produksi tempe sorgum sesuai jumlah pertumbuhan responden, mencari sumber sorgum yang siap olah dari daerah lain. Strategi S-T antara lain memacu beberapa riset aksi multi-tahun pada lahan basah dan kering di Kab. Musi Rawas, mengutamakan peralatan lokal tanpa bahan  kimia, memastikan pakai teknik produksi unggul berproduktivitas tinggi dan hemat lahan dan strategi  W-T antara lain memilih daerah dan petani yang siap dibina menanam sorgum sesuai kebutuhan, menyediakan diklat khusus tentang produksi tempe sorgum higienis dan berkualitas, menyediakan gudang sorgum yang baik di dekat produsen.